Gamma knife for the treatment of choroidal breast cancer metastasis causing retinal detachment: A case report - Ong, Jee Yan; Alfian, Ereena; Kumar, Ramesh; Ismail, Fuad; Ho, Niki Wai Wye; Bastion, Mae-Lynn Catherine; Othman, Othmaliza (Frontiers in Oncology, 2025)
IntroductionChoroidal metastasis generally has poor prognosis and most commonly originates from breast carcinomas. While systemic chemotherapy offers therapeutic benefits, local therapies are often necessary for symptom management and tumor control. Gamma knife radiosurgery (GKR), which was originally developed for intracranial lesions, has emerged as a promising treatment for choroidal metastasis, offering high precision and minimized toxicity with fewer ocular side effects compared with conventional radiotherapy. This case report explores the use of GKR in a patient with choroidal and brain metastases from breast carcinoma.Case presentationA 44-year-old woman with a history of treated left breast carcinoma presented with 3 months’ gradual vision loss in her left eye. Her visual acuity at presentation was counting fingers (CF). Imaging revealed a choroidal metastasis along with multiple brain metastases. The patient underwent GKR for both choroidal and intracranial metastases, receiving doses ranging from 16 to 18 Gy at 50%–90% isodose. Following treatment, significant tumor regression was observed, with a marked reduction in retinal detachment and vision improvement to 6/18. At 6 months post-GKR, both the choroidal mass and the retinal detachment had fully resolved; however, her visual acuity remained limited due to foveal atrophy.ConclusionThis case demonstrates the potential of GKR as a noninvasive and effective modality for the simultaneous treatment of choroidal and intracranial metastases. In palliative settings, especially for patients with limited life expectancy, GKR can provide symptomatic relief and improved quality of life with minimal invasiveness, which is particularly valuable for younger patients facing advanced metastatic cancer. The importance of a multidisciplinary approach in the management of complex metastatic diseases is also highlighted. Future studies are warranted to fully define the role of GKR in choroidal metastasis and its long-term sequelae.